Approaches of dengue control: vaccine strategies and future aspects - Akter, Runa; Tasneem, Faria; Das, Shuvo; Soma, Mahfuza Afroz; Georgakopoulos-Soares, Ilias; Juthi, Rifat Tasnim; Sazed, Saiful Arefeen (Frontiers in Immunology, 2024)
Dengue, caused by the dengue virus (DENV), affects millions of people worldwide every year. This virus has two distinct life cycles, one in the human and another in the mosquito and both cycles are crucial to be controlled. To control the vector of DENV, the mosquito Aedes aegypti, scientists employed many techniques, which later proved ineffective and harmful in many ways.Consequently, the attention shifted to the development of a vaccine; researchers have targeted the E protein, a surface protein of the virus and the NS1 protein, an extracellular protein. There are several types of vaccines developed so far, such as live attenuated vaccines, recombinant subunit vaccines, inactivated virus vaccines, viral vectored vaccines, DNA vaccines and mRNA vaccines.Along with these, scientists are now looking for new strategies for developing an improved version of the vaccine by employing recombinant DNA plasmid against NS1 by trying to prevent the infection by blocking the DENV life cycle inside the mosquito. Here, we discussed the aspects of research in the field of vaccines until now and identified some prospects for future vaccine developments.